Institutional and legal approach to eldercare versus sustainable work concept in selected European Union countries - Furmańska-Maruszak, Agnieszka; Kamińska, Katarzyna (Ekonomia i Prawo. Economics and Law, 2018)
Motivation: European societies face the problem of ageing populations and shrinking labour force. One of the ways to tackle this issue is the development of sustainable approach towards work. Sustainable work means creating such living and working conditions that they enable people to remain in employment throughout their extended working life. It requires gaining adequate skills, adjusting working conditions for elder workers’ needs as well as helping them balance work and life. Family obligations are not only related to childcare but also to eldercare given to parents, step-parents or spouses. The balance between work and care might be supported both at the enterprise and the institutional level. Aim: The article aims to examine the legal and institutional approach to care for the elderly in the selected EU countries (Germany, the UK, Finland and Poland) and to answer the question to what extent these institutions and laws support the concept of sustainable work. Results: The extent to which national institutions and laws support sustainable work concept differ between countries, depending on the welfare model they represent. Finland represents Nordic welfare model in which publicly organised and financed eldercare is very generous, so sustainable work model is easy to put in practice. German welfare state also has its social policy well developed, and care systems are supported by the universal long-term care insurance. The UK is an example of a more liberal regime, in which sustainable work concept is more market-driven. Polish efforts to follow the German model with reference to social insurance are still under public debate. However, we doubt whether German solutions are possible to be introduced in Polish conditions due to the different position of trade unions in this country, less importance of employee participation in company management than in Germany, and definitely less than in Germany the regulation of the labor market. In Poland, informal institutions, such as family and cultural customs, play a much greater role in organizing help in the care of an elderly person. Formal institutions play a smaller role in the organization of this care. We propose to take some solutions at the national and enterprise level to raise awareness of the need to take steps to address the issue of support for employees caring for an elderly person.